2018
DOI: 10.1002/ajb2.1116
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive differentiation among populations of the Mediterranean dry grassland species Brachypodium retusum: The role of soil conditions, grazing, and humidity

Abstract: Adaptive population differentiation in germination and early growth may have contributed to different colonization patterns. Thus, the provenance of B. retusum needs to be carefully considered in ecological restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Four seeds of each experimental plot (block × treatment combination) were sown to one plug. The plug trays were placed in a growth chamber under optimum germination conditions (temperature 15/20°C, 12/12 h night/day — Vidaller et al., ) and watered regularly. Coleoptile emergence was used as a proxy of germination and was recorded every 2–3 days for seven weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four seeds of each experimental plot (block × treatment combination) were sown to one plug. The plug trays were placed in a growth chamber under optimum germination conditions (temperature 15/20°C, 12/12 h night/day — Vidaller et al., ) and watered regularly. Coleoptile emergence was used as a proxy of germination and was recorded every 2–3 days for seven weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Brachypodium retusum is still widespread in the Mediterranean region but also suffers from the loss of this habitat. In ecological restoration, Brachypodium retusum shows poor re‐establishment (Coiffait‐Gombault, Buisson, & Dutoit, ; Vidaller, Dutoit, Ibrahim, Hanslin, & Bischoff, ) and it is obvious that restoration remains incomplete if the dominant species of pristine steppes is lacking. Thus, a better knowledge on the ecology of the species and on the effects of major management factors is needed to better conserve these plant communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the major climatic factor varying in the study region is rainfall increasing from the east to the west. In a previous common garden study on a subset of populations, significant differentiation was found between soil types within sites with the same climate, although differentiation between sites of different climate was much stronger (Vidaller et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…In the French part of the B. retusum range, two major environmental gradients have been identified. First, the species occurs on calcareous soils of lower mountain ranges and on decarbonated red Mediterranean soils of former river valleys but is absent from lowlands with deep clay and loam soils (Vidaller et al, 2018). Second, the major climatic factor varying in the study region is rainfall increasing from the east to the west.…”
Section: Introductionmentioning
confidence: 97%